2015
DOI: 10.1371/journal.pone.0133664
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine-Induced Adrenergic Activation Strikingly Increased the Atrial Fibrillation Duration through β1- and α1-Adrenergic Receptor-Mediated Signaling in Mice

Abstract: BackgroundAtrial fibrillation (AF) is the most common arrhythmias among old people. It causes serious long-term health problems affecting the quality of life. It has been suggested that the autonomic nervous system is involved in the onset and maintenance of AF in human. However, investigation of its pathogenesis and potential treatment has been hampered by the lack of suitable AF models in experimental animals.ObjectivesOur aim was to establish a long-lasting AF model in mice. We also investigated the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…Thereby, the blockade of α 1 -adrenoceptors may lead to the stabilization of Ca 2+ level producing antiarrhythmic effect in arrhythmias induced by catecholamines e.g., catecholaminergic polymorphic ventricular tachycardia. The above hypothesis was supported by Suita et al ( 2015 ), who demonstrated that prazosin not only shortened norepinephrine-induced elongation of atrial fibrillation in mice, but also attenuated norepinephrine-induced SR Ca 2+ leak and spontaneous SR Ca 2+ release in cultured atrium cardiomyocytes. This proves that α 1 -adrenoceptors may have role in preventing cardiac arrhythmias.…”
Section: Introductionmentioning
confidence: 74%
“…Thereby, the blockade of α 1 -adrenoceptors may lead to the stabilization of Ca 2+ level producing antiarrhythmic effect in arrhythmias induced by catecholamines e.g., catecholaminergic polymorphic ventricular tachycardia. The above hypothesis was supported by Suita et al ( 2015 ), who demonstrated that prazosin not only shortened norepinephrine-induced elongation of atrial fibrillation in mice, but also attenuated norepinephrine-induced SR Ca 2+ leak and spontaneous SR Ca 2+ release in cultured atrium cardiomyocytes. This proves that α 1 -adrenoceptors may have role in preventing cardiac arrhythmias.…”
Section: Introductionmentioning
confidence: 74%
“…We previously demonstrated that the sympathetic activation by intraperitoneal administration of norepinephrine (NE) (1.5 mg/kg) strikingly elongated the duration of AF in mice. 23 The sympathetic activation-induced elongated AF was also shorter in Epac1-KO mice (WT vs. Epac1-KO: 716.49± 174.20 s vs. 215.19±70.94 s, P<0.05) ( Figure 1D). These findings indicate that Epac1 plays an important role in the development of AF in mice.…”
Section: Epac1 Deficiency Shortened the Duration Of Afmentioning
confidence: 87%
“…Simple and minimally invasive AF was induced in mice by transesophageal burst pacing, and the duration of AF (AFD) was measured, as previously reported. 23 Briefly, the mice were anesthetized under isoflurane (1.5%) inhalation. For 10 s, the transesophageal atrial burst pacing was conducted at a stimulation of 1.5 mA with 10-ms cycle lengths and a pulse width of 3 mA.…”
Section: Induction Of Afmentioning
confidence: 99%
“…In our report, 85 (55.2%), 26 (16.9%) and 74 (48.1%) subjects were treated with amiodarone,propafenone and metoprolol, respectively. As we know, amiodarone slows conduction rate and prolongs the refractory period of the SA and AV nodes; 23 propafenone slows the influx of sodium ions into the cardiac muscle cells, causing a decrease in excitability of the cells; 24 and metoprolol blocks β1 adrenergic receptors in heart muscle cells, thereby decreasing the slope of phase 4 in the nodal action potential and prolonging repolarization of phase 3 25 . In general, these medicines are mainly to control arrhythmia by affecting the action potential of cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%